F2R-CWANA Morocco Inception Workshop Program - Baum, Michael; Al-Zu'bi, Maha; Crichton, Rhiannon (2023)
The brochure contains information on the background of the F2R-CWANA Initiative, rationale for implementation in Morocco and an itemized workshop program.